A survey of modernist poetry / Laura Riding and Robert Graves. - Jackson, Laura (Riding), 1901-1991; Graves, Robert, 1895-1985 (Hassell Street Press, 2023)
This study of modernist poetry by Laura (Riding) Jackson and Robert Graves collects their main collaborative critical works, in which they produce a contemporary reaction to the early century experimentalism of such writers as Eliot, Pound and Cummings.